The effectiveness of promotional tools in influencing purchase decision on cctv products - GYIMAH REXFORD (KNUST, 2024)
A thesis presented to the institute of distance learning, Kwame Nkrumah university of science and technology, Kumasi, in partial fulfillment of the requirements for the award of master of science in marketing